Influence of oak trees on soil hydraulic characteristics: A spatial analysis in a Mediterranean silvo-pastoral ecosystem - Hassan Awada; Simone Di Prima; Pier Paolo Roggero; Mario Pirastru (Journal of Hydrology, 2026)

Trees control hillslope subsurface flow: Insights from stemflow and throughfall experiments, geophysical surveys, and numerical modeling - Simone Di Prima; Gersende Fernandes; Maria Burguet; Maria Paz Salazar; Elisa Marras; Ilenia Murgia; Konstantinos Kaffas; Luca Peruzzo; Ryan D. Stewart; Majdi R. Abou Najm; Alessandro Comegna; Laurent Lassabatere; et al. (Journal of Hydrology, 2026)

Modeling water infiltration into soil under fractional wettability conditions - Simone Di Prima; Ryan D. Stewart; Majdi R. Abou Najm; Deniz Yilmaz; Alessandro Comegna; Laurent Lassabatere (Journal of Hydrology, 2025)

Spatio-temporal variation of surface soil hydraulic properties under different tillage and maize-based crop sequences in a Mediterranean area - Rasendra Talukder; Daniel Plaza-Bonilla; Carlos Cantero-Martínez; Simone Di Prima; Jorge Lampurlanés (Plant and Soil, 2024)
Aims The surface crust formed by the drop impact of rainfall and/or irrigation is a prevalent characteristic in many Mediterranean soils. However, the temporal variation of soil hydraulic properties induced by surface crust during the high-frequency irrigation has rarely been investigated. Methods Beerkan infiltration tests in conjunction with the BEST method were used to investigate the effects of surface crusting on the spatio-temporal variation of saturated soil hydraulic conductivity ( K s , mm s −1 ), sorptivity ( S , mm s −0.5 ), mean pore size ( r , mm), number of effective pores per unit area ( N , m −2 ) in Agramunt, NE Spain. Results In response to autumn tillage, intensive tillage (IT) increased K s and S due to higher r and N , but both declined after 60 days. Reduced tillage (RT), maintained comparable K s and S values, despite having a lower N value. After the spring tillage, both IT and RT developed crusted layers, resulting in decreased K s , S and N . Long-term no-tillage (NT) showed an increasing trend of K s and S over time, except for the last sampling. Spatial variation (i.e., between the rows, B-row vs. within the row of crops, W-row) of K s and S was found, and non-crusted soils (W-row) had consistently higher K s and S than crusted soils (B-row). Conclusions Conservation tillage i.e., RT and NT improve the surface soil structure and reduce the risk of crust development. Surface cover by crops may help to prevent crust formation within the row of crops, improving soil hydraulic conductivity.

Analysis of critical water flow and solute transport parameters in different soils mixed with a synthetic zeolite - Alessandro Comegna; Claudia Belviso; Anna Rita Rivelli; Antonio Coppola; Giovanna Dragonetti; Ameneh Sobhani; Simone di Prima; Antonio Satriani; Francesco Cavalcante; Stella Lovelli (CATENA, 2023)

Evaluating subsurface flow connectivity in a pine-covered hillslope with stemflow infiltration and ground-penetrating radar surveys - Simone Di Prima; Gersende Fernandes; Elisa Marras; Filippo Giadrossich; Ryan D. Stewart; Majdi R. Abou Najm; Thierry Winiarski; Brice Mourier; Rafael Angulo-Jaramillo; Alessandro Comegna; Antonio del Campo; Laurent Lassabatere (Journal of Hydrology, 2023)

Beerkan multi-runs for characterizing water infiltration and spatial variability of soil hydraulic properties across scales - Laurent Lassabatere; Simone Di Prima; Rafael Angulo-Jaramillo; Saskia Keesstra; David Salesa (Hydrological Sciences Journal, 2019)